2017
DOI: 10.1002/2016jg003569
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter compositions of rivers draining into Hudson Bay: Present-day trends and potential as recorders of future climate change

Abstract: Concentrations and compositions of particulate and dissolved organic carbon (POC and DOC, respectively) and aromatic compounds including lignin were analyzed in water samples from 17 rivers flowing into Hudson Bay, northern Canada. These rivers incorporate basins to the south with no permafrost to basins in the north with continuous permafrost, and dominant vegetation systems that include Boreal Forest, the Hudson Plains, Taiga Shield, and Tundra. Major latitudinal trends in organic carbon and lignin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 85 publications
(155 reference statements)
3
25
0
Order By: Relevance
“…This would be in line with Godin et al. (2017), Kalbitz et al. (2000), and Raymond and Hopkinson (2003) who also found that DOM contains mainly young components by 14 C dating.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This would be in line with Godin et al. (2017), Kalbitz et al. (2000), and Raymond and Hopkinson (2003) who also found that DOM contains mainly young components by 14 C dating.…”
Section: Discussionsupporting
confidence: 89%
“…The dating of the DOM in the various ecosystem solutions supports our hypothesis that DOM in rainfall originated from fresh plant tissue in the forest canopies and in the mineral soil solutions from canopy leachates, aboveground and belowground litter, or root exudates. This would be in line with Godin et al (2017), , and Raymond and Hopkinson (2003) who also found that DOM contains mainly young components by 14 C dating.…”
Section: Sources and Age Of Domsupporting
confidence: 89%
“…The compositional lignin phenol parameters S/V, and C/V ranged from 0.32 to 0.48, and 0.06 to 0.13, respectively, and did not exhibit substantial changes with locations and time ( Table 1 and Figure 4). S/V and C/V are generally employed to explore sources of tDOC (i.e., angiosperm versus gymnosperm and woody versus nonwoody) (Hedges and Mann, 1979;Goñi and Hedges, 1995;Godin et al, 2017). Representative tissues and their leachates were integrated in Figure 4 to aid with identification of tDOC sources ( Supplementary Table S1).…”
Section: Concentrations and Distributions Of Doc And Biochemicalsmentioning
confidence: 99%
“…As a result, these large systems are unlikely to be representative of the distributed array of smaller watersheds that comprise a significant proportion of the Arctic basin. Measurements characterizing the biogeochemistry of smaller rivers in Alaska (Townsend‐Small et al, ), Siberia (Johnston et al, ), around Hudson Bay (Godin et al, ), and in the Canadian Arctic Archipelago (Alkire et al, ) have provided well‐defined estimates of water chemistry, but over relatively constrained spatial scales, or—because of logistical constraints—based on a relatively small number of samples. In Canada in particular, we know little about the 75% of the Arctic‐flowing drainage that lies outside of the well‐characterized Mackenzie system (see also Alkire et al, and Godin et al, , for recent progress).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements characterizing the biogeochemistry of smaller rivers in Alaska (Townsend‐Small et al, ), Siberia (Johnston et al, ), around Hudson Bay (Godin et al, ), and in the Canadian Arctic Archipelago (Alkire et al, ) have provided well‐defined estimates of water chemistry, but over relatively constrained spatial scales, or—because of logistical constraints—based on a relatively small number of samples. In Canada in particular, we know little about the 75% of the Arctic‐flowing drainage that lies outside of the well‐characterized Mackenzie system (see also Alkire et al, and Godin et al, , for recent progress). This lack of knowledge exists despite evidence of increasing fluxes of dissolved carbon and ions from several Canadian Arctic locations, which appear to be driven by thawing permafrost and other factors related to climate change (Kokelj et al, ; Spence et al, ; Tank et al, ).…”
Section: Introductionmentioning
confidence: 99%